Hopping on trends Risa Hontiveros’ TikTok politainment as image-building strategy - Dalit, Tracy Kate N.; Suarez, Gerard Martin C. (Quezon City University of the Philippines Diliman, 2025)
The intersection of media, politics, and culture has led to the mediatization of politics, resulting in an increased political spectacle. This gave birth to pop politics and contributed to the shifting dynamics of political communication shaped by the rhythms of new media platforms, making social media the new ‘political stage.’ Given this, many politicians have resorted to social media to maximize their online presence by amplifying politainment or the intertwining of politics and entertainment (Nieland, 2008). That said, this thesis is a qualitative content analysis that examines how Senator Risa Hontiveros, a political oppositional and minority figure in the Philippines, facilitated her image-building strategy in TikTok post-elections. Guided by Stuart Hall’s (1997) Representation Theory, particularly the Constructionist View of the representation process, this study explored Hontiveros' TikTok politainment content by studying the (1) visual, linguistic, and auditory composition of her videos, (2) the employed strategy in her content production, and (3) her image representation in the said platform. This study
found that Hontiveros utilizes TikTok politainment as a tool for image-building by merging policy-driven and entertainment-driven content to sustain relevance and visibility, as well as to create a favorable image that appeals to her target audiences.
Thesis
Keywords: Hontiveros, Risa; Women politicians -- Philippines -- Public opinion; Social media -- Political aspects -- Philippines